2022
DOI: 10.1136/bmjopen-2021-052555
|View full text |Cite
|
Sign up to set email alerts
|

Safety, feasibility, acceptability and preliminary effects of the Neurofenix platform for Rehabilitation via HOMe Based gaming exercise for the Upper-limb post Stroke (RHOMBUS): results of a feasibility intervention study

Abstract: ObjectivesTo investigate the safety, feasibility and acceptability of the Neurofenix platform for home-based rehabilitation of the upper limb (UL).DesignA non-randomised intervention design with a parallel process evaluation.SettingParticipants’ homes, South-East England.ParticipantsThirty adults (≥18 years), minimum 12-week poststroke, not receiving UL rehabilitation, scoring 9–25 on the Motricity Index (elbow and shoulder), with sufficient cognitive and communicative abilities to participate.InterventionsPar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…A total of 45 studies 15,1721,23,2629,33,35,36,40,42,43,45,46,49,5256,6166,68,69,71,72,74,77–79,8285,89,91 deployed games for home-based upper limb rehabilitation following stroke. Of these, 15 articles 15,18,20,28,29,33,35,42,45,46,56,72,82,84,91 found a VR game to be a feasible, well-received, and safe intervention to use at home for people with chronic hemiparesis following stroke. These studies also demonstrated a positive impact of VR games on improving arm functioning and the number of reaching movements achieved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 45 studies 15,1721,23,2629,33,35,36,40,42,43,45,46,49,5256,6166,68,69,71,72,74,77–79,8285,89,91 deployed games for home-based upper limb rehabilitation following stroke. Of these, 15 articles 15,18,20,28,29,33,35,42,45,46,56,72,82,84,91 found a VR game to be a feasible, well-received, and safe intervention to use at home for people with chronic hemiparesis following stroke. These studies also demonstrated a positive impact of VR games on improving arm functioning and the number of reaching movements achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies 12,14,20,21,24,25,30,34,37,48,50,51,60,61,67,7375,80,86,91,94 used a mobile technology or a mobile application as part of their intervention for home-based upper limb rehabilitation with stroke patients. Mobile technology had been used more frequently by stroke patients for information searching, and reminders in comparison to non-stroke participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations